Giant triple negative pregnancy-associated breast cancer (PABC) in a young woman: From diagnosis to therapy step by step: A case report - Micol Bottalico; Cristiana Boldrini (Radiology Case Reports)
Pregnancy-associated breast cancer (PABC) presents unique challenges. This type of breast cancer is often more aggressive than that diagnosed in nonpregnant women, and its diagnosis is frequently delayed. Several factors contribute to this delay, including the physiological changes that occur during pregnancy, such as breast enlargement, breast tenderness and increased tissue density, which can mask early signs of malignancy. Additionally, a lack of awareness among healthcare providers can lead to symptoms being dismissed as normal pregnancy-related changes, and then being underestimated. Consequently, PABC is often diagnosed at more advanced stages, which can result in a poorer prognosis for the patient. This case study reports a 36-year-old woman in good general health, who received histological diagnosis of breast cancer during her pregnancy after presenting for self-detection of an enormous palpable breast mass. Prior to hospitalization, the patient had been treated with antibiotics in the mistaken belief that it was infectious mastitis; subsequently, considering the huge dimensions of the mass and the presence of lymph node metastases, neoadjuvant chemotherapy was started until induction of labor. Imaging techniques such as ultrasonography (and mammography as an adjunct) and nonenhanced MRI (due to potential toxicity of gadolinium to the fetus) can be used for staging maternal breast disease during pregnancy. A multidisciplinary approach which involves the radiologist, the breast surgeon, the oncologist and the gynecologist is fundamental to ensure the best prognostic outcomes for both the mother and the fetus.